Sosialisasi Memaksimalkan Produk Eksploitasi Buah Kelapa Menjadi VCO Yang Berpotensi Untuk Meningkatkan Pendapatan Masyarakat Dalam Perspektif Islam Desa Kuala Lagan Kabupaten Tanjung Jabung Timur - Ridhwan; Amir, Amri; Enggrani Fitri, Lucky; Lubis, Paulina; Aprizal, Yusuf Zaini (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
This community service activity aims to fulfill daily life. Coconut is one of the superior commodities which is very abundant in Kuala Lagan Village. However, this potential has not been optimized due to the lack of understanding and experience of the community in developing coconut fruit exploitation products into VCO to increase community income. Community income from an Islamic perspective in Kuala Lagan Village, East Tanjung Jabung Regency is based on the potential that the village community already has. Based on the problems above, it is necessary to increase understanding through community empowerment to support and increase community creativity in utilizing coconuts to become VCO to increase income from an Islamic perspective. This program aims to develop and provide socialization and assistance to the community so that they can optimize the village's potential.